Impacto do excesso de peso nos determinantes clinicopatológicos do câncer de mama e sua associação com os níveis de citocinas, estresse oxidativo sistêmicos e marcadores tumorais - Silva, Adma Poliana De Borba Cecilio da (2023)
Breast cancer is the most incident neoplasm among women in the world. Although obesity consists of a pro-inflammatory disease and is considered a critical agent for the development of breast cancer, the impact of the obesogenic state on the regulation of antitumor immune responses and its influence on clinical determinants of disease prognosis is still little discussed. . Thus, this study aims to evaluate the impact of excess weight on clinicopathological determinants of breast cancer and its change with circulating levels of cytokines and systemic oxidative stress. The present work is a cross-sectional observational study carried out at the Hospital do Câncer de Francisco Beltrão - PR, with 195 women diagnosed with breast cancer before the start of treatment, from May 2015 to January 2022, with analysis of clinicopathological information, measurement of circulating levels of cytokines (IL-4 and IL-12), experience of the redox profile (hydroperoxides and metabolites of nitric oxide - NOx) and tumor tissue expression of iNOS, TGF-β1, CD4 and CD8. Participants were subdivided into two groups according to BMI: normal (up to 24.9 kg/m2) and overweight (BMI ≥ 25.0 kg/m2). Subsequently, these groups were compared, both in terms of clinicopathology and serum levels (cytokines and redox profile) and expression of iNOS, TGF-β1, CD4 and CD8 in the tumor infiltrate. The frequency of women with histological grade 3 was higher in the overweight group. IL-4 levels were significantly increased in the overweight group and were associated with luminal B molecular subtypes, presence of lymph node metastasis, and age at diagnosis ≤ 50 years. IL-12 dosages increased only in the overweight and lymph node metastasis group. NOx levels in the overweight group were increasing in patients with Luminal B subtype, histological self grade and lymph node metastases. Hydroperoxide levels when comparing normotrophic and overweight patients showed significant differences with increase in tumors smaller than 2 cm compared to normotrophic patients with the same tumor size profile. The expression of iNOS was increased in tumor biopsies from patients with BC and overweight compared to eutrophic women, as well as the CD4 infiltrate was significantly increased in the overweight group. Together, our data provide evidence that there may be a correlation between systemic and tumor tissue immune responses influenced by excess weight when the disease is already established, with increases in IL-4 and NOx, as well as expression of iNOs and CD4 in the tumor environment.